Fragility functions for reinforced-concrete frames classified by joint strength margin: the case of interior beam–column joint - Takashi Takeuchi; Hajime Okano; Kazutaka Shirai (Journal of Asian Architecture and Building Engineering)
Probabilistic approaches using fragility functions effectively assess building damage caused by major earthquakes and consequent repair costs. Existing fragility functions, however, are limited to reinforced concrete (RC) frames designed according to U.S. standards, making them unsuitable for frames designed according to other design standards. This study addresses this limitation by developing fragility functions for RC frames with interior beam – column joints classified based on joint strength margins. These margins were calculated using the joint ultimate strength relative to the ultimate strengths of beams and columns, enabling evaluations independent of design standards. Damage states (DSs) from DS1 to DS3 were defined to represent residual cracking, concrete damage, and ultimate state, respectively, with DS3 further subdivided into DS3–1 and DS3–2. Relationships between story drift ratios at damage states and joint strength margins were analyzed using Japanese experimental data. RC frames were ranked by joint strength margins, and a Bayesian approach was applied to evaluate fragility function parameters for each DS across these ranks.